THE USE OF STUDENT TEAMS-ACHIEVEMENT DIVISION IN TEACHING SIMPLE PAST TENSE - Mauludiana, Poppy Iga; Sudarsono, Sudarsono; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research investigated the evidence whether using Student Teams-Achievement Division as a teaching technique was useful to teach students simple past tense. It was a pre-experimental research with one group pre-test and post-test design. There were 34 students (X IIS 4 learning group) who participated in this research. The data were collected by written tests and analyzed by t-test. According to the research findings, the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. The obtained t-value (9.23) was bigger than the critical value of r (1.692) by the degree of freedom 33. It was concluded that the use of STAD is significant and very effective to teach simple past tense to Year?10 students of ?SMA Negeri 7 Pontianak? in Academic Year 2017/2018. Key Words: Student Teams-Achievement Division, Simple Past Tense, Recount Text